Investigation of infinite focus microscopy for the determination of the association of blood with fingermarks. Issue 6 (November 2018) - Deininger, L.; Francese, S.; Clench, M.R.; Langenburg, G.; Sears, V.; Sammon, C.
Abstract: The determination of the type of deposition mechanism of blood within fingermarks at the scene of violent crimes is of great importance for the reconstruction of the bloodshed dynamics. However, to date, evaluation still relies on the subjective visual examination of experts. Practitioners encounter three types of scenarios in which blood may be found in fingermarks and they refer to the following three deposition mechanisms: (i) blood marks, originating from a bloodied fingertip; (ii) marks in blood, originating from a clean fingertip contacting a blood contaminated surface; (iii) coincidental deposition mechanisms, originating from a clean fingertip contacting a clean surface, leaving a latent fingermark, and subsequent contamination with blood. The authors hypothesised that, due to differences in distribution of blood in the furrows and on the ridges, the height of blood depositions on the ridges and furrows (and their relative proportions), will differ significantly across the three depositions mechanisms. A second hypothesis was made that the differences would be significant and consistent enough to exploit their measurement as a quantitative and objective way to differentiate the deposition mechanisms. In recent years, infinite focus microscopy (IFM) has been developed, allowing for the computational generation of a 3D image of the topology of a sample via acquisition of images on multiple focal planes. On these bases, it was finally hypothesised that the application of this technique would allow the distinction of deposition mechanisms (i) to (iii). A set of preliminary experiments were designed to test whether IFM was "fit for purpose" and, subsequently, to test if any of the three deposition mechanisms scenarios could be differentiated. Though IFM enabled the analysis of tape lifted samples with some success, for samples produced and analysed directly on the surface of deposition, the results show that the measurements from any scenario will be highly dependent on the original surface of deposition (both in terms of its nature and of the variable exposure to environment); as crime scenes exhibit a wide range of possible relevant surfaces of deposition, the technique showed to not have the desired wide appeal for inclusion into a standardised set of protocols within a routine crime scene workflow. Graphical abstract: Highlights: IFM enables reproducible topographical measurements regardless of sample orientation. IFM enables the measurement of the height of ridges and blood in blood fingermarks. IFM enables the topographical quantitative assessment of lifted blood marks. Surfaces roughness/wettability prevents IFM topographical assessment of blood marks.